REPRESENTASI KARAKTERISTIK MASYARAKAT BERBUDAYA PADA FILM ANIMASI - Chandra, Ni Putu Mertha Natania (Pusat Penerbitan LPPM ISI Bali, 2025)
Animation is a form of art that is popular among today's society, especially among us teenagers. Animation has a unique ability to communicate traditional values and cultural identity. Animation can strengthen the cultural identity of a society by using traditional visuals in a modern form. This research will discuss how community characteristics can be reflected through cultural representation in animation which includes elements such as traditional clothing, language, customs and narratives originating from local community myths and local history. The results of this research will show that animation is able to represent culture authentically and is an important tool in maintaining the sustainability of cultural heritage.